Scoping Review: Physical Activity and Social Functioning in Young People With Autism Spectrum Disorder - Reinders, Nicole J.; Branco, Alexandra; Wright, Kristen; Fletcher, Paula C.; Bryden, Pamela J. (Frontiers in Psychology, 2019)
Autism Spectrum Disorder (ASD) affects approximately 1 in 59 people in North America and diagnoses continue to rise (Centre for Disease Control and Prevention, 2018). Unfortunately, the exact cause of ASD is unknown and therapy remains the primary means of intervention. People with ASD experience social and behavioural deficits associated with the disorder, which affect all aspects of life such as academics, relationships, and physical activity. Research has shown a relationship between physical activity and social skills in typically developing individuals; however, this relationship is less well understood in people with ASD. The purpose of this scoping review was to uncover what is known about ASD, physical activity, and social functioning. The authors searched four databases and included 40 primary research articles in the review, most of which demonstrated a relationship between physical activity and social functioning for people with ASD. The relationship appears bidirectional: social functioning influences physical activity (to a lesser extent) and physical activity influences social functioning (to a greater extent). Regrettably, there were many limitations in these articles, such as small sample sizes and the under-representation of females and adults. Therefore, the review highlights several directions for future research.